Trends in incidence, prevalence, and mortality of non-communicable diseases in Iraq (2003–2021) - Mohammed Merzah (BMC Public Health)
Abstract Background Non-communicable diseases (NCDs) have become a major public health concern in Iraq, playing a significant role in the country’s morbidity and mortality rates. To offer a thorough overview of the patterns and the overall impact of NCDs on public health, this study aims to map the trends in the incidence, prevalence, and mortality rates of NCDs in Iraq between 2003 and 2021. Methods Data from the Global Burden of Disease (GBD) Study 2021 were utilized. The focus was on Iraq from 2003 to 2021, a period marked by significant social and political changes. Using the GBD results tool, age-standardized prevalence, incidence, and mortality rates (ASPR, ASIR, ASMR) for 12 major NCDs were extracted and expressed per 100,000 population. Descriptive statistics with 95% uncertainty intervals were calculated, and trends were analyzed. Results The analysis revealed a nuanced trajectory of NCDs in Iraq between 2003 and 2021. The ASPR of all NCDs increased slightly (change %: 0.1, 95% UI: -2.2 to 2.4), with a notable decline in chronic respiratory diseases (change %: −14.4, 95% UI: (-30.9 to 6.1) and a significant rise in neoplasms (change %: 32.7, 95% UI: -5.9 to 81.3). The ASIR of diabetes and kidney diseases showed the largest increase (change %: 42.9, 95% UI: 28.4 to 59.3), while chronic respiratory diseases had the greatest decline (change %: −12.1, 95% UI: -36.8 to 22.5). Cardiovascular diseases remained the leading cause of mortality in both sexes, with ASMRs increasing slightly for males and decreasing for females over the period. Skin and subcutaneous diseases showed the highest increase in ASMR (change %: 48.2), while digestive diseases experienced the largest decline (change %: −21.4). Conclusion The GBD 2021 study highlights progress in reducing NCD mortality in Iraq, especially among younger people. However, older males still face high death rates from cardiovascular diseases. Rising cases of cancer, diabetes, and kidney diseases signal the need for targeted interventions. Continued focus on risk factors and healthcare access is essential.